PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI (Studi Kasus pada Perusahaan Sub Sektor Asuransi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Puteri Utami, Dena Hesa (Aksara Public, 2018)
This research aims to know the influence of Good Corporate Governance which is proxy by the institutional Ownership, Independent Commissioner, and the Audit Committee of the Firm Value with Financial Performance as the Moderate Variable (Case Study on the Insurance Sub Sector Companies listed on the Indonesia Stock Exchange Period 2013-2016). The population of this research is the insurance sub sector companies listed on the Indonesia Stock Exchange period 2013-2016. Based on the selection of the sample there are 8 company that examined for 4 years with 32 samples. A data analysis method in this research is the regression data panels and Moderate Regression Analysis (MRA) using Eviews software 9. The result of this research shows that good corporate governance before and after moderated financial performance has significantly to the firm value. It means that, with the improvement of the mechanism of good corporate governance and financial performance will show up investor confidence so were able to increase the firm value.